ANALISIS IMPLEMENTASI KEBIJAKAN PEMBENTUKAN DAERAH OTONOM BARU (DOB) PROVINSI PAPUA TENGAH - Cahyadi, M Fikri; Kurniawan, Teguh (Jurnal Politik Pemerintahan Dharma Praja, 2021)
DOB can improve public services and realize the effectiveness of governance in the regions. The parameters used through the Ratio of Human Resources, Apparatus, Economy, Education, Health, Population and Regional Fiscal are the benchmarks that the formation of DOB in improving public services can be realized. This writing uses a qualitative approach with the method of collecting data from literature studies (literature review) through documentation related to research in the form of a strategic study, thesis and dissertation on the formation of DOB, as well as through legislation related to research. The results of the writing show that synergy in coaching, mentoring and efforts to improve services to the community in the implementation of DOB towards advanced and independent autonomous regions can be measured through parameters to achieve the targets set in services to the community. Keywords: Autonomous Regions, DOB, Public Services, Local Government.